2008
DOI: 10.2337/db08-0153
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Melanocortin-4 Receptor Deficiency in Europeans and Their Age-Dependent Penetrance in Multigenerational Pedigrees

Abstract: OBJECTIVE-Melanocortin-4 receptor (MC4R) deficiency is the most frequent genetic cause of obesity. However, there is uncertainty regarding the degree of penetrance of this condition, and the putative impact of the environment on the development of obesity in MC4R mutation carriers is unknown.RESEARCH DESIGN AND METHODS-We determined the MC4R sequence in 2,257 obese individuals and 2,677 nonobese control subjects of European origin and established the likely functional impact of all variants detected. We then i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
216
4
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(249 citation statements)
references
References 38 publications
(55 reference statements)
23
216
4
6
Order By: Relevance
“…One sister studied for the MC4R gene has the obese phenotype but does not carry the p.H76R mutation. This result is in concordance with the literature stating that this MC4R missense mutation is not associated with the morbid obesity phenotype (Stutzmann et al, 2008).…”
Section: Pedigree B Mc4r Ph76r Mutationsupporting
confidence: 93%
See 2 more Smart Citations
“…One sister studied for the MC4R gene has the obese phenotype but does not carry the p.H76R mutation. This result is in concordance with the literature stating that this MC4R missense mutation is not associated with the morbid obesity phenotype (Stutzmann et al, 2008).…”
Section: Pedigree B Mc4r Ph76r Mutationsupporting
confidence: 93%
“…Other authors defended an age-related penetrance for MC4R deficiency and demonstrated a generational effect on penetrance, related to the development of an "obesogenic" environment. It may contribute to the coexistence of obese noncarrier individuals among relatives of those strongly genetically predisposed (Stutzmann et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This locus is monomorphic for the valine allele in the 426 Pima Indians in whom the gene was sequenced. A recent meta-analysis in a large group of Europeans found that a range of functional MC4R variants were more common in obese than lean individuals (28). In a German population study, R165Q was rare (minor allele frequency 1.2 ϫ 10 Ϫ4 ) and the individual was not obese (26).…”
Section: Discussionmentioning
confidence: 99%
“…As MC4R deficiency is the most common genetic form of obesity, assessment of the sequence of the MC4R is increasingly seen as a necessary part of the clinical evaluation of the severely obese child. Other genetic and environmental modifiers can affect the degree of obesity associated with MC4R mutations in some pedigrees (Stutzmann et al 2008), as such co-dominance, with modulation of expressivity and penetrance of the phenotype, seems an appropriate descriptor for the mode of inheritance (Farooqi et al 2003).…”
Section: Disorders Affecting Melanocortin Signallingmentioning
confidence: 99%